Marketing Nursing: An Approach Related to Nursing Profession - Bimi, Indrit (Research Papers, 2023)
Nurse’s profession trends are counted a lot of them, but some of the most important are nursing shortage, retention, and job satisfaction which are different in several countries.We have to say that the 4Ps approach and the nursing profession are well connected and can improve each health organization and nursing profession like other professions.Internal marketing and nurses’ job satisfaction are new trends but very important so we cannot be faced with a turnover of the health workforce in our countries.In the end, we can conclude that marketing is very important for nurses and is not vulgar commercialism. This approach is related mostly to the 4ps approach and internal marketing, especially with the job satisfaction of nurses.